A Description of the Risk for Delirium in Residents Living with Diabetes in Long-Term Care Homes Across Ontario - Heale, Roberta; Gorham, Robyn; Rietze, Lori; Hill, Laura (European Scientific Journal, ESJ, 2024)
Aim: The aim of this study was to explore risk factors of delirium for residents with diabetes in LTC in Ontario. Scope: Residents in long term care (LTC) are vulnerable to negative outcomes related to diabetes, including delirium. Understanding factors related to the risk of delirium for residents with diabetes provides the foundation for mitigation of delirium in this population. Methods: A population-based retrospective secondary analysis was conducted using a dataset from the Resident Assessment Instrument – Minimum Data Set of residents living in LTC settings in Ontario between April 1, 2019, and March 31, 2020. Findings: Results showed that delirium was significantly associated with diabetes. Additionally, residents with diabetes had a higher occurrence of other delirium risk factors, including behavioural symptoms of dementia and the use of multiple medications, such as analgesics and psychotropic medications. Conclusions: Strategies to mitigate delirium in this population should be implemented.